High Plasma Concentration of Apolipoprotein C-III Confers an Increased Risk of Cerebral Ischemic Events on Cardiovascular Patients Anticoagulated With Warfarin - Olivieri, Oliviero; Turcato, Gianni; Cappellari, Manuel; Stefanoni, Filippo; Osti, Nicola; Pizzolo, Francesca; Friso, Simonetta; Bassi, Antonella; Castagna, Annalisa; Martinelli, Nicola (Frontiers in Cardiovascular Medicine, 2022)
INTRODUCTION: Apolipoprotein C-III (Apo CIII) is a crucial regulator of triglyceride-rich lipoproteins (TRLs) and influences the risk of cardiovascular diseases. High levels of Apo CIII have been also associated with cerebrovascular events and earlier works showed procoagulant effects of Apo CIII. The main aim was to assess whether the plasma concentration of Apo C-III could confer an increased risk of cerebral ischemic events in anticoagulated patients at high-risk of cardioembolism. METHODS: We systematically checked medical records and quantified cerebral ischemic events in a selected cohort of 118 subjects (median age 68 with interquartile range (IQR) 59-75 years, 66.9% males, 52.5% with coronary artery disease (CAD)), taking anticoagulant therapy with warfarin because of atrial fibrillation (AF) and/or mechanical prosthetic heart valves. All the subjects, enrolled between May 1999 and December 2006, were prospectively followed until death or July 31, 2018. Assessments of complete plasma lipid and apolipoprotein profiles, including Apo A-I, B, CIII, and E, were available for all subjects at enrollment. RESULTS: After a median follow-up of 109 months (IQR, 58-187), 24 subjects (20.3%) had cerebral ischemic events: stroke (n=15) and TIA (n=9). Subjects with plasma concentration of Apo C-III above the median value (10.3 mg/dL) had an about three-fold increased risk of stroke/TIA than those with lower levels of Apo C-III (hazard ratio 3.08 [95%CI, 1.22-7.77]). This result was confirmed in multiple Cox regression models adjusted for gender, age, CAD, AF, diabetes, hypertension, plasma lipids, and CHA2DS2-VASc score. By stratifying the sample on the basis of Apo C-III level and CHA2DS2-VASc score, an additive effect was observed with the highest risk in subjects with both high Apo C-III concentration and CHA2DS2-VASc score. CONCLUSIONS: High Apo CIII plasma levels may be associated with an increased risk of ischemic stroke/TIA in high-risk cardiovascular patients anticoagulated with warfarin.